Pemberian Dini Vasopresor pada Syok Sepsis - Ferianto Ferianto; Ezra Oktaliansah; Indriasari Indriasari (Fakultas Kedokteran Universitas Riau, 2020)
Sepsis is life-threatening organ dysfunction caused by a dysregulated host response to infection and become one of leading causes of death in Intensive Care Unit (ICU). The two components of treating sepsis shock are fluid resuscitation and administration of vasopressor. Early administration of vasopressor in conjunction with fluid administration can reduce mortality because it reduces the volume of resuscitation so as to prevent excess fluid in the patient. Recent recommendation from Surviving Sepsis Campaign (SSC) suggest fluid resuscitation and medication within the first 1 hour including vasopressor administration in concomitant life-threatening cases of hyptension or immediately after fluid resuscitation to maintain MAP level ≥ 65mmHg. Holistic treatment will reduce the mortality of patient with sepsis shock in the ICU